FROM OBSERVATIONS TO INSTITUTIONS : RISE OF METEOROLOGICAL SCIENCE IN COLONIAL BENGAL, 1784 – 1905 - Sinha, Sohini (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The last few decades have witnessed flowering of interest in the history of western science in colonial India. The study of the knowledge forms of non-western societies is a rapidly emerging research field that could have a lasting impact on the disciplinary history of science (Raina, 2010, p.1). The present paper tries to explain the nature of the development and evolution of the modern meteorological science in colonial Bengal, to explore the complex relationship between science and colonisation.